The effects of tillage and long-term irrigation on dynamic soil properties and genesis of Aridic Argiustolls in western Kansas - Scarpace, Michelle Rose (Kansas State University, 2016)
Soil is a dynamic resource that can undergo many changes due to altering conditions (Tugel et al., 2005). With that, humans can have a great effect on the conditions of a landscape and contribute to soil change. As soils change, the function of soils can be altered which would affect the ability of soils to support ecosystem services. The objective of this thesis is to access how management affects dynamic and inherent soil properties in western Kansas soils. Eight sites in Sheridan County, KS mapped as Keith 1-3% slopes (fine-silty, mixed, superactive, mesic Aridic Argiustolls) were described and sampled. Of the eight sites, four are in ST (ST) management and four are in no-till (NT) management. All sites have been irrigated under center pivot irrigation systems since the 1970s. Soil samples of the A horizon were taken at each site to analyze total carbon, aggregate stability, bulk density, pH and microbial respiration to assess the impacts of tillage management on dynamic soil properties. Additionally, pedons were described from the ST sites in the irrigated areas as well as outside the pivot track to represent dryland conditions. Particle size data, field descriptions, and the micromorphology of thin sections were analyzed to determine if the classification of Keith soils are affected by irrigation. Significant differences between NT and ST management were seen in microbial respiration, select water stable aggregate sizes, and pH and bulk density at certain depths. It was also found that irrigation did not affect clay illuviation nor carbonate leaching. Overall, it was concluded that inherent soil properties such as soil map unit composition and parent material can have a greater impact on soil change and prevent the recognition of changes in soil properties over a human time scale.
Keywords: Dynamic soil properties; Soil genesis; Pedology